2016
DOI: 10.1016/j.jgeb.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and plant regeneration of Capsicum baccatum L.

Abstract: A plant regeneration protocol via somatic embryogenesis was achieved in cotyledon and leaf explants of Capsicum baccatum, when cultured on MS medium supplemented with various concentrations of 2,4-dichlorophenoxy acetic acid (2,4-D, 0.5–5.0 mg l−1) in combination with Kinetin (Kn, 0.5 mg l−1) and 3% sucrose. Various stages were observed during the development of somatic embryos, including globular, heart, and torpedo-stages. Torpedo stage embryos were separated from the explants and subcultured on medium suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
1
8
0
4
Order By: Relevance
“…This showed that the somatic embryo development process is asynchronous. Similar results have been found in Hibiscus sabdariffa (Konar et al 2018), Akebia trifoliata (Zou et al 2019), Helianthus annuus L. (Fu et al 2017), and Capsicum baccatum (Venkataiah et al 2016). Finally, when the cotyledonary stage embryos were sub-cultured in MS medium containing 1 mgL -1 BAP at 12 WAC, they were converted into complete plantlets (Figure 1.G).…”
Section: Induction Of Embryogenic Calli Developmentsupporting
confidence: 84%
“…This showed that the somatic embryo development process is asynchronous. Similar results have been found in Hibiscus sabdariffa (Konar et al 2018), Akebia trifoliata (Zou et al 2019), Helianthus annuus L. (Fu et al 2017), and Capsicum baccatum (Venkataiah et al 2016). Finally, when the cotyledonary stage embryos were sub-cultured in MS medium containing 1 mgL -1 BAP at 12 WAC, they were converted into complete plantlets (Figure 1.G).…”
Section: Induction Of Embryogenic Calli Developmentsupporting
confidence: 84%
“…Previous studies suggested that 2,4-D was necessary for SE in several species such as Capsicum baccatum [21], Tagetes erecta [22], Salicornia brachiate [23] and Cymbopogon winterianus [24]. High indirect somatic embryogenesis from immature embryos of buckwheat also occurred on B 5 medium with 6% sucrose when 5.0 mgL −1 2,4-D and 0.1 mgL −1 KT were supplied at the beginning of the culture period for 5 days, and then transferred to B 5 medium plus 2.2 mgL −1 BAP, 0.17 mgL −1 IAA for germination of somatic embryos [14].…”
Section: Discussionmentioning
confidence: 98%
“…Under these conditions, embryos continued germinating, shoots and roots started developing within 17-20 days. The resulat is similar with some other reports on different plant like (Bhattacharya ., 2016), (L.) F. Muell (Shekhawat & Manokari, 2016) and (Venkataiah , 2016). Further growth of plantlets was done on the same basal MS medium containing 0.5mg/L BAP.…”
Section: Methodsmentioning
confidence: 99%